Determinar los factores de riesgo más frecuentes y modificables con un plan de cuidados de enfermería en mujeres embarazadas con preclampsia que son atendidas en el Hospital Sagrado Corazón de Jesús de Quevedo año 2012 - Vera Barboto, Mónica Cecibel (2013)
The development of this project aims to determine the most common risk factors and modifiable with a plan of nursing care in pregnant women with preeclampsia who are treated at Sacred Heart Hospital de Quevedo 2012. Background.- In the Hospital “Sacred Heart of Jesus Quevedo Canton " , there were 112 cases of preeclampsia , of which 42 cases are teenagers and 54 cases over 35 years, the rest of different ages , data were taken from the medical history patients. Objective Determine the risk factors influencing the incidence of preeclampsia in women of Sacred Heart Hospital de Quevedo. Methodology The study is descriptive quantitative approach of the data obtained in the first stage of research, we sought to determine pathological conditions the incidence of preeclampsia in mothers treated at Sacred Heart Hospital in Quevedo. This stage has been implemented through a matrix having indicators according to the objectives outlined in the Research. Results and Conclusions Most patients diagnosed with preeclampsia had a low educational level, prenatal deficiency and residence in rural areas which shows that the behavior of social and environmental factors predisposing to the onset of preeclampsia. This is an urgent health issue, which should disclose as many women lack knowledge of what is preeclampsia plus those living in rural areas.